Implosion : lessons from national security, high reliability spacecraft, electronics, and the forces which changed them - Temple, L. Parker; Wiley eBooks (Hoboken, New Jersey : Wiley/IEEE Press, 2013)
High reliability electronics engineering is one of the key driving forces for economic recovery. This book offers a focused study of the history and uses of high reliability solid state electronics, military standards, and space systems that support national security and defense. Unique in combining the interdependent evolution of and interrelationships among military standards, solid state electronics, and very highreliability space systems, it offers essential knowledge for those in the fields of aerospace, engineering, instrumentation, measurement, testing, and quality control.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Electronics -- United States -- History -- 20th century; Electronics in military engineering -- United States -- History -- 20th century; Electronics; Electronics in military engineering; United States; 1900-1999; Electronic books